Ancaman Kebijakan Ekspor Pasir Laut terhadap Keamanan Maritim Indonesia - Karen, Christie; Rosnani, Rosnani; Erlangga, Raditya (Universitas Bosowa, 2025)
This study examines the implications of the sea sand export policy for Indonesia’s maritime security. The policy had been suspended for 20 years due to losses suffered by Indonesia, particularly concerning maritime boundary issues with Singapore, but was reopened under the administration of President Joko Widodo through Government Regulation (PP) No. 26 of 2023 on the Management of Marine Sedimentation. The policy has sparked debates and controversy, as it is considered to potentially threaten Indonesia’s maritime security. This study employs a descriptive qualitative method, using data collected from literature sources, including press releases, policy documents, and relevant scholarly articles.